A country study : Sri Lanka (2006)
[Dt.:] A Country Study: Sri Lanka ist ein Projekt der Federal Research Division des Library of Congress. Diese Seiten bieten einfache und verständliche Einführungen und einen Überblick zu Geschichte, Kunst und Kulturen Sri Lankas. - [Engl.:] A Country Study: Sri Lanka is a project of the federal Research Division of Library of Congress. These pages provide simple and comprehensible introductory overviews to history, art and cultures of Sri Lanka